2015
DOI: 10.3390/ijerph13010047
|View full text |Cite
|
Sign up to set email alerts
|

Computer Optimization of Biodegradable Nanoparticles Fabricated by Dispersion Polymerization

Abstract: Quality by design (QbD) in the pharmaceutical industry involves designing and developing drug formulations and manufacturing processes which ensure predefined drug product specifications. QbD helps to understand how process and formulation variables affect product characteristics and subsequent optimization of these variables vis-à-vis final specifications. Statistical design of experiments (DoE) identifies important parameters in a pharmaceutical dosage form design followed by optimizing the parameters with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Numerical optimization searches the design space, using the developed regression model to find the factor settings that optimize any combination of one or more goals. It finds a point that maximizes this desirability function [33]. To find the global (overall) desirability function, the Design-Expert software carries out thousands of calculations, and finally, it provides the maximum desirability score and the sets of conditions on which it has arrived.…”
Section: Simultaneous Optimization Of Friability and Disintegration Tmentioning
confidence: 99%
“…Numerical optimization searches the design space, using the developed regression model to find the factor settings that optimize any combination of one or more goals. It finds a point that maximizes this desirability function [33]. To find the global (overall) desirability function, the Design-Expert software carries out thousands of calculations, and finally, it provides the maximum desirability score and the sets of conditions on which it has arrived.…”
Section: Simultaneous Optimization Of Friability and Disintegration Tmentioning
confidence: 99%
“…Importantly, it was indicated that the inlet temperature of the fluid-bed granulator was the most significant factor (p < 0.05) for the LOD, as shown in Table 4. Furthermore, lack of fit was not significant factor (p = 0.1978), which proves that this model is appropriate for our adjustments [18]. Fig.…”
Section: Evaluation Of Wet Granulationmentioning
confidence: 57%
“…The average observation data (data before stability assay) is compared to the prediction interval (both 95% PI low and high). Table 4 showed that the observation data from confirmation runs of all four parameters were within the confirmation 95% prediction interval, where PI is point prediction indicating that the model can accurately predict the value of all parameters of the optimal formula (Akala et al, 2015). Based on Table 4, the optimal formula resulted in non-aqueous gel with good characteristics such as pH of the formulation was within skin physiological pH value, can easily be spread on the skin due to high spreading diameter and low viscosity but also has good adhesion to the skin.…”
Section: Results and Discussion Optimization Of Peg 400 And Propylene...mentioning
confidence: 94%